Taṭbīq at-Ṭarīqah al-Qiyāsiyyah Wa Uslūb NHT Bi al-Biṭṭāqah at-Takammulah Li Tarqiyah Qudrah aṭ-Ṭālibāt `Alā Fahm al-Qawā`id an-Naḥwiyyah Bi Ma`had Dār al-Iḥsān - Moch Fajarul Falah; Dewi Susanti (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
Al-Qawa’id al-Nahwiyyah is one of three important elements in a language. The students should learning qawa’id to know the correct last line of the word in arabic language, then to help them in increasing their speaking and writing well and right by a good language. So that, the researcher used the qiyasiyyah and uslub NHT by using bitaqah takammulah for increasing student’s achievment to comprehend qawa’id nahwu at Darul Ihsan school. Because after the researcher make the observation, the researcher found many of mistake and error language structure, the students express the error example in making some sentence (error language structure), beside of the tehnique or media in teaching learning process was not interesting. The purpose of the research is to know the effectiveness of the application of qiyasiyyah and uslub NHT by using bitaqah takammulah for increasing student’s achievment to comprehend qawa’id nahwu at Darul Ihsan school, also how far the student’s response after applied it. In this research the researcher used true-experimental method with post-test only control group design. The population of this research is all the students of MTsS Darul Ihsan, consist of 740 students, in this case the researcher used random sampling by cluster tehnique and the researcher took two classes as sample and those are class 2f dan 2e. The instrument of this research is the test and questionnaire after analizing the data, the result of this research shown that the result of ttest was higher than ttabel in significant standard 5% was 7,36 > 2,00. Base on the research result, the researcher conclude that the application of Tariqah Qiyasiyyah and uslub NHT by using bitaqah takammulah is effective for increasing student’s achievement in comprehend qawa’id nahwu at Darul Ihsan boarding school.